Manajemen Pembiayaan Pendidikan Berbasis Akuntabilitas dalam Meningkatkan Mutu Layanan Sekolah Menengah Atas - Trian Hermawan; Binti Luthfiyah; Undang Rosidin (WISE Pendidikan Indonesia, 2026)
This study aims to analyze accountability-based educational financing management in improving the quality of senior high school services. This study employed a qualitative-conceptual approach using an integrative literature review design involving nine relevant articles on educational financing management, school financial management, accountability, transparency, school funding, and service quality in education. The data were analyzed through thematic-critical synthesis by identifying patterns of findings, comparing the contributions of each article, and formulating a conceptual framework for accountability-based educational financing management. The findings indicate that financial accountability is not merely related to administrative compliance or financial reporting, but also functions as a strategic governance principle that connects needs-based budgeting, participatory allocation, disciplined implementation, transparent reporting, supervision, and quality-oriented evaluation. The findings also reveal that the involvement of principals, treasurers, teachers, school committees, and other stakeholders is essential to ensure that school funds are used effectively, equitably, and meaningfully to improve learning services. This study concludes that accountability-based educational financing management can serve as a governance framework for strengthening the quality of senior high school services. The implication is that schools need to develop a transparent, well-documented, participatory, and benefit-evaluation-based financing system so that educational funds contribute directly to sustainable educational service quality.